Navigating Engagement in the New Normal of Telework: Cultural Differences between France and Canada - Falcon, Gaëlle; Klarsfeld, Alain; Saba, Tania (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2025)
The shift to telework has significantly transformed traditional work environments, introducing new dynamics in employee relationships and organizational structures. Telework is now mainstream, but it also presents new challenges for employee engagement. To address these challenges, effective management requires processes aimed at improving employees’ sense of engagement. This study compares the effects of three variables, organizational fairness, trust in/by managers, and trust in/by colleagues, on teleworkers’ psychological engagement in Canada and France. Based on a PLS-SEM analysis on two samples of 196 participants in France and 454 in Canada, findings show that organizational fairness is a key common antecedent of teleworkers' engagement in both countries. They also revealed strong cultural differences: trust in and by managers is crucial in Canada, while trust in and by colleagues is significant in France.